The Educational Environmental Concepts in the Geography Curriculum for Basic Eighth Grade from the Teachers' Point of View – A field Study in Lattakia City - ياسين, أحلام; برغل, سومر; غانم, آنا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims to identify the opinion of teachers about the educational environmental concepts contained within the geography book for basic eighth grade from the teachers point of view, also identify the difference in their opinion according to variables (sex, scientific and educational qualification, experience, training courses). To achieve the aims of research, used the descriptive analytical approach, and the researcher prepared a questionnaire has been included (36) methods about the educational environmental concepts contained within the geography book for basic eighth grade, then the validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Tishreen and Tartous Universities. Pilot sample consisted of (26) teachers. Reliability was established through Cronbach – Alpha (0.961), and (0.962) through Spearman-Brown, which indicate to high reliability to questionnaire. research sample consisted of (58) teachers for the academic year 2019/2020. The most important results of the research, that total degree of educational environmental concepts contained within the geography book for basic eighth grade from the teachers point of view came out at a middle degree, and There was no statistically significant differences between respondents degrees returns of the research sample to the (sex and experience) variables, while the results showed significant differences according to the scientific and educational qualification variable in favour of Education Preparation Diploma and postgraduate studies, also to the training courses variable in favour of the teachers whom proceeded the training.